Differences in post‐exercise inflammatory and glucose regulatory response between sedentary indigenous australian and caucasian men completing a single bout of cycling. Issue 2 (28th December 2013) - Mendham, Amy E.; Duffield, Rob; Marino, Frank; Coutts, Aaron J
ABSTRACT Objectives This study compared the acute inflammatory and glucose responses following aerobic exercise in sedentary Indigenous Australian and Caucasian men, matched for fitness and body composition. Methods Sedentary Indigenous (n = 10) and Caucasian (n = 9) Australian men who were free from chronic disease volunteered to participate. Following baseline testing, participants completed a 40 min cycling bout at ∼80% maximal heart rate. Fasting venous blood was collected pre, 0, 30, 60, and 240 min post‐exercise for analysis of glucose, insulin, cortisol, tumor necrosis factor (TNF)‐α, interleukin (IL)‐1β, IL‐6, IL‐1 receptor agonist (ra), and C‐reactive protein (CRP). Results Resting TNF‐α and glucose concentrations were significantly higher in the Indigenous group (P < 0.05). IL‐6 and IL‐1ra were elevated for longer in Caucasian (P < 0.05), compared with the Indigenous group (P > 0.05). The post‐exercise (0 min) increase in cortisol and glucose for the Caucasians was higher (P < 0.05) than the attenuated responses within the Indigenous group (P > 0.05). Conclusions Despite being matched for fitness and body composition the Indigenous men had elevated resting TNF‐α and glucose compared with the Caucasian men, which may have contributed to the suppressed post‐exercise anti‐inflammatory response of the Indigenous men; however, glucose normalized between groups post‐exercise. As such, it is recommended for acute moderate‐intensity exercise to be completed daily for long‐term improvements in glucose regulation, irrespective of ancestry. Of note, results suggest it to be even more pertinent for exercise to be encouraged for Indigenous Australian men due to their elevated resting glucose levels at a younger age, when compared to the respective Caucasian group. Am. J. Hum. Biol. 26:208–214, 2014. © 2013 Wiley Periodicals, Inc.